2018
DOI: 10.3390/molecules23102604
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Antifungal Activity of Pyridine-Based Triple Quaternized Chitosan Derivatives

Abstract: In this study, a series of triple quaternized chitosan derivatives, including 6-O-[(2-hydroxy-3-trimethylammonium)propyl]-2-N-(1-pyridylmethyl-2-ylmethyl)-N,N-dimethyl chitosan chloride (7), 6-O-[(2-hydroxy-3-trimethylammonium)propyl]-2-N-(1-pyridylmethyl-3-yl- methyl)-N,N-dimethyl chitosan chloride (8), and 6-O-[(2-hydroxy-3-trimethylammonium)propyl]- 2-N-(1-pyridylmethyl-4-ylmethyl)-N,N-dimethyl chitosan chloride (9) were successfully designed and synthesized via reacting epoxypropyl trimethylammonium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…t-Acon possesses several peaks, with the most representative being those between 1727 and 1700 cm −1 owing to the –COOH fragments. CS-tAcon derivative exhibits the carbonyl group peak at 1718 cm −1 , implying the successful introduction of t-Acon group to the CS structure [ 45 ]. In parallel with the previous data, CS-Succ displays a new peak at 1728 cm −1 matching to the free carboxyl groups after the modification of –NH 2 CS groups with succinic anhydride, while the successful modification of CS chains is revealed by the formation of new amide bonds [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…t-Acon possesses several peaks, with the most representative being those between 1727 and 1700 cm −1 owing to the –COOH fragments. CS-tAcon derivative exhibits the carbonyl group peak at 1718 cm −1 , implying the successful introduction of t-Acon group to the CS structure [ 45 ]. In parallel with the previous data, CS-Succ displays a new peak at 1728 cm −1 matching to the free carboxyl groups after the modification of –NH 2 CS groups with succinic anhydride, while the successful modification of CS chains is revealed by the formation of new amide bonds [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polymeric networks can be swollen due to alterations in their external environment. Additionally, polymeric materials containing hydrophilic groups swell to a higher degree compared to those containing hydrophobic groups since the chemical structure of a polymer directly affects its swelling capacity [ 45 ]. As a result, hydrophobic groups lead to a breakdown in the appearance of water [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…(Ali & Wilson, 2017;Kariduraganavar et al, 2014;Lee et al, 2004;Lim et al, 2008;Niu et al, 2017). In this work, polyhexamethylene guanidine hydrochloride (PHMGH) was evaluated for its F I G U R E 4 Modified derivatives of chitosan which have shown potentiated antifungal properties (Tan et al, 2017(Tan et al, , 2018Wei et al, 2018;Zhang et al, 2020) F I G U R E 5 Formation of nylon-3 derivatives from ring-opening polymerization of substituted β-lactams antifungal properties (Figure 6). The authors found that this polymer has comparable MICs to AmB against various fungi species (Table 2), while causing no haemolysis or LDH release at concentrations at least up to 16 times higher than the found MICs (in direct contrast with AmB which is much more toxic to human cells).…”
Section: A Final Series Of Examples Of Chitosan Modification Is the Workmentioning
confidence: 99%
“…In this work (Figure 4a), a combination of phosphonium and ammonium salts was introduced by chitosan amine groups alkylation and nucleophilic substitution to form the quaternary alkyl and allyl phosphonium groups (Tan et al, 2017). In another paper (Figure 4b), the research group modified chitosan nitrogen with two methyl groups and a different array of pyridinium groups through Schiff base intermediates to form quaternary ammonium antifungal polymers (Wei et al, 2018). In a follow‐up study (Figure 4c), the same research group used azide––alkyne click reactions to include quaternary ammonium onto chitosan (Tan et al, 2018).…”
Section: Polymers With Antifungal Moietiesmentioning
confidence: 99%
See 1 more Smart Citation